Al-Qur’an Solusi Paripurna: Menyelami Konsep-Konsep Al-Quran Dalam Memberantas Kemiskinan Ber-Multidimensi - Kahar, Abd.; Hayati, Nur; Fadilah, Nor (International Conference on Islamic Studies, 2021)
This article tends to discover the secrets of Al-Quran in eradicating poverty in some aspects, by collecting some verses that are not only in line with physical aspect but also spiritual and social one, then analized by using thematic-analitical method of interpretation. The result, to eradicate that multidiminsional proverty should evolve three aspects of way, that are, first: the aspect of spiritual that is related to Allah vertically; second, the personal aspect that is related to his effort to reduce even erase that poverty; third, social sensitivity aspect that is related to his self as a carefull individu to others as being cared that need his carefullness.